SUGGESTIVE AGE TO INITIATION IN SPORTS KARATE: A PERSPECTIVE OF KARATE TEACHERS, PHYSICAL EDUCATION PROFESSIONALS AND PEDIATRICIANS DOCTORS (Fiep Bulletin - online, 2013)
This study aimed to determine the optimal age for initiation in sports karate on the perspective of karate teachers, physical education professionals and pediatricians. Karate is a martial art or fight systematized in Japan. In Brazil this fight is widely practiced in schools, gyms and clubs, where the largest number of practitioners is composed of children. Was formulated then the question of investigative activity guide: what the optimal age for initiation Karate? It was a comparative and descriptive study, qualitative and quantitative. The research sample consisted of 10 teachers of Karate, 10 Physical Education Professionals and six pediatricians. Data collection was performed by the application of a subjective questionnaire to those involved. The teachers of this fight and pediatricians indicated, mostly, the ideal age for initiation of the practice of Karate as five years. But authors like Carazzato and Costa (1991), Weineck (2000) and Figueiredo (2003) reinforce the view of Physical Education professionals participating in the study, which is six years for the ideal age for this sport initiation fight. The study includes the opinion of Physical Education teachers is the most consistent, given the academic background of these, making them experts in the field, and also by the statement authors reference area, which also teach that the age of six years is the ideal initiation to the sport.
Keywords: Initiation Sports; Karate; Child